Evaluation of Program For Funding Assistance for Beginner Entrepreneurs: A Case in Universitas Terbuka - Durri Andriani (Pelopor Publikasi Akademika, 2023)
This research examines the impact of the Entrepreneurship Development Assistance Program initiated by the Ministry of Cooperatives and SMEs through the Field of Entrepreneurship Development and Human Resource Development on Open University (UT) students. In 2015, the Ministry provided financial support and limited training and mentoring to UT students to foster entrepreneurship. The program is monitored over two years, from the student submitting a business proposal to funding, and is extended to the next three semesters. Students interested in starting their own business must submit a proposal, which is evaluated for feasibility and potential funding. This research involves contacting students who have participated in the 2015 Program. A total of 266 program participants were identified as the target population for the study. These participants came from Bandung, Batam, Denpasar, Jember, Jogjakarta, and Semarang. By equipping student entrepreneurs with adaptability and resilience, the program has the potential to foster a culture of entrepreneurship and contribute to economic growth and innovation in the long run.